Assessment of prevalence of acute respiratory tract infection and risk factors in under five children in anganwadi of Kota city - Temani, Kuldeep; Mayenger, Amrita; Bairwa, A L (Indian Journal of Child Health, 2016)
Background: Acute respiratory tract infection (ARI) is a major cause of morbidity and mortality in developing countries. Objective: To find out the prevalence and risk factors related to ARI among children between 0 and 5 years attending anganwadi centers in Kota city. Materials and Methods: A community-based, prospective, cross-sectional study was carried out in 14 Integrated Child Development Services center (seven zones) of Kota city covering 406 under five children during March 2015-February 2016. Results: The overall prevalence of ARI was 32% (130/406). Winter season, illiterate mother, >2 under five children at home, overcrowding, smoker in house, family member suffering from cough and cold in last month, smoky chullhas, low birth weight (LBW), partial immunization, inappropriate breastfeeding were significant risk factors for ARI. No association was found between prevalence of ARI and age, sex, religion of child, geographic location of house in terms of main road, place of birth (home or hospital), and birth order of the child. Conclusion: The prevalence of ARI was 32%. Significant risk factors were illiterate mother, more than two under five children at home, overcrowding, LBW, partial immunization, lack of exclusive or short duration of exclusive breastfeeding, use of biomass fuel, smoker in house, family history of cough and cold in last month, and kitchen attached to living room.